Research on How to Design an Android-based RFID Reader - Lian Lu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Android is a very popular system in Chinese mobile phone market, while radio frequency identification device (RFID) which is originally used in fields of retail and logistics etc.. is going to be installed into Android to realize the visualization of commodity information (including the updating, discounting, and after-sale service) and the general use for publics. This study firstly discussed the overall design requirements of an Android platform-based RFID reader. Subsequently, basing on design positioning and principle, the design idea and parameters involved in the design realization were given a detailed description. Design was completed with the aid of related mobile phone applications developed by Android smart phone and multi-level technology testing and research. The new design is attempt to build a new technological life in future and further improve life quality.